2022
DOI: 10.3390/ijerph192316268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Paraben Exposure on Adiposity-Related Measures: An Updated Literature Review of Population-Based Studies

Abstract: Parabens are alkyl esters of p-hydroxybenzoic acid that are commonly used in pharmaceutical and cosmetic products. Humans are exposed to parabens when they use these products and through diet. There are growing concerns that paraben exposure can adversely impact human health. The endocrine-disrupting and obesogenic properties of parabens have been observed in animal studies and in vitro, prompting the increase in population-based studies of paraben exposure and adiposity-related endpoints. In this review, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Parabens are known endocrine disruptors that are able to activate PPARs, TRs, and glucocorticoid receptors (GRs). In a recent review on the obesogenic effect of prenatal exposure to parabens, Xu et al [ 67 ] concluded that despite the evidence from in vitro and animal studies, there are several discrepancies regarding population-based studies, which are probably due to the inherent limitations of the studies. Interestingly, it is worth highlighting that although most of these studies confer an obesogenic effect to most parabens (butylparaben, methylparaben, or propylparaben), prenatal exposure to ethylparaben (EtP) has been described to be associated with lower birth weights and lower BMI z-scores [ 35 , 68 ].…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…Parabens are known endocrine disruptors that are able to activate PPARs, TRs, and glucocorticoid receptors (GRs). In a recent review on the obesogenic effect of prenatal exposure to parabens, Xu et al [ 67 ] concluded that despite the evidence from in vitro and animal studies, there are several discrepancies regarding population-based studies, which are probably due to the inherent limitations of the studies. Interestingly, it is worth highlighting that although most of these studies confer an obesogenic effect to most parabens (butylparaben, methylparaben, or propylparaben), prenatal exposure to ethylparaben (EtP) has been described to be associated with lower birth weights and lower BMI z-scores [ 35 , 68 ].…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…Parabens are alkyl esters of p-hydroxybenzoic acid that are used as preservatives in cosmetics, personal-care products, pharmaceuticals, and food [52]. In vitro, parabens promoted lipid accumulation and increased mRNA expression of adipocyte-specific markers (Pparγ, C/ebpα, Fabp4, and fatty acid synthase (Fas) in murine 3T3-L1 cells and human adipose-derived multipotent stem cells (ASCs) [53].…”
Section: Parabensmentioning
confidence: 99%